"Could We Just Breathe for 30 Seconds?": Social Worker Experiences of Holistic Engagement Practice Training. Issue 4 (30th August 2021) - Pyles, Loretta; Cosgrove, Darren T; Gardner, Erin; Raheim, Salome; Adam, Gwendolyn J; Chakravarty, Sreyashi; Cooke, Collina
Abstract: Given the still emerging evidence base about the effectiveness of practices, such as mindfulness, somatics, and integrative body-mind-spirit social work, there is a need to know more about the impacts that training in such areas can have on social workers and their professional work. This mixed-methods article reports on a pilot study that explored practitioners' perceptions regarding the impact of learning holistic engagement practice (HEP) skills on their service delivery and well-being. The research inquires into the perceptions of social workers who received the training, particularly in relation to their quality of presence and the therapeutic relationship; HEP as a form of self-care and a facilitator of compassion satisfaction; the impact it has on social work practice and settings; and the facilitators and barriers to using holistic engagement. Implications from the findings focus on the need for additional research, training, organizational change, and communities of practice to facilitate changes that could promote more effective social work practice, greater levels of empathy, and compassion satisfaction.